2009
DOI: 10.1016/j.bbmt.2008.12.506
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Stem Cell Transplantation Compared with Chemotherapy for Poor-Risk Hodgkin Lymphoma

Abstract: The aim of this study was to assess the role of allogeneic hematopoietic stem cell transplantation (HSCT) in patients with poor-risk Hodgkin's disease (HD) compared to chemotherapy. A donor was identified in 26 patients (14 HLA identical siblings and 10 alternative donors), and 24 received a transplant (Allo group). Twenty patients without a donor received different chemotherapy regimens and radiotherapy (CHEMO group). After a median follow-up of 28 months (range: 1-110), the 2-year overall survival (OS) was 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…14,22 However, the long-term results have been quite discouraging, mainly because of high relapse rates. In our study, 52% of the patients relapsed, a finding that agrees with earlier reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,22 However, the long-term results have been quite discouraging, mainly because of high relapse rates. In our study, 52% of the patients relapsed, a finding that agrees with earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective reports have evaluated allogeneic transplantation after full intensity conditioning [3][4][5][6] and several more recent studies have evaluated allogeneic transplantation after reduced intensity conditioning (allo-RIC). [7][8][9][10][11][12][13][14][15] In these trials, the selected patients were in an advanced disease stage and heavily pre-treated and both TRM and the relapse rates were high. The present trial, the first national compilation study, summarises experiences of allogeneic transplantation after reduced intensity conditioning in adult HL patients in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports in the literature demonstrate that allogeneic transplantation, when feasible, can really improve survival. [26][27][28] Despite the lower nonrelapse mortality associated with the procedure, resulting from the development of reduced intensity conditioning regimens, allogeneic transplantation remains controversial. 29 In particular, such a procedure is often reserved for patients in at least partial response after salvage treatment and chemorefractory patients never benefit from allogeneic transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Nevertheless, with both approaches, long-term progression-free survival curves did not exceed 20% to 25% in most of the studies. [12][13][14][15][16][17] Moreover, data regarding the responses to donor lymphocyte infusions (DLIs) are conflicting, thus questioning the existence of the postulated "graft-versus-HL effect." [13][14][15][16][17][18] To date, only 1 retrospective study suggested the superiority of RIC alloSCT over conventional "non-SCT" therapies in patients relapsing after an autoSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Moreover, data regarding the responses to donor lymphocyte infusions (DLIs) are conflicting, thus questioning the existence of the postulated "graft-versus-HL effect." [13][14][15][16][17][18] To date, only 1 retrospective study suggested the superiority of RIC alloSCT over conventional "non-SCT" therapies in patients relapsing after an autoSCT. 19 To evaluate the role of RIC alloSCT as a realistic salvage option in the clinical setting, we performed a retrospective analysis on patients relapsing after an autoSCT.…”
Section: Introductionmentioning
confidence: 99%